Nazwy ulic wsi gminy Nakło nad Notecią - Duszyński-Karabasz, Henryk (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The article presents the street names of the five villages in the district of Nakło nad Notecią (Paterek, Potulice, Ślesin, Trzeciewnica, Występ). The semantic analysis have shown the main naming types and also the similarities and differences between the naming systems of each village. The most popular street name types are topographic and natural names. Over 85% of all plateonyms have the adjectival form. This is the most productive structural type in the viconymy.